How to Sustain Visitors’ Interest during The Crisis: The Case Study of Pangandaran Beach - Ribka Nauli Sitorus; Tomy Andrianto; Dinarsiah Chendraningrum (Journal of Tourism Sustainability, 2022)
Pangandaran, one of Indonesia's well-known tourist destinations, has never been vacant when allowed to visit, even during the COVID-19 Pandemic. This study aims to understand the factors that that sustain visitors' interest in Pangandaran during the COVID-19 Pandemic. Qualitative description was used in this study by conducting semi-structured interviews with eleven visitors visiting Pangandaran during a pandemic. This study found five main factors that sustained visitors' interest in visiting Pangandaran during the Pandemic. First is the internal factor in traveling to the beach, longing for the atmosphere and nature of Pangandaran. Second is the distance, and the third is the popularity of Pangandaran. Four factors are the destination's affordable facilities, such as hotels and Restaurants. Last is the strategic location of the west and east coast meet at the same destination. Those five factors accumulated a strong power that sustains visitor's interest in visiting Pangandaran even in crises such as Pandemic Covid-19.